2018
DOI: 10.1016/j.bbi.2018.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Associations between maternal cytokine levels during gestation and measures of child cognitive abilities and executive functioning

Abstract: Preclinical studies demonstrate that environmentally-induced alterations in inflammatory cytokines generated by the maternal and fetal immune system can significantly impact fetal brain development. Yet, the relationship between maternal cytokines during gestation and later cognitive ability and executive function remains understudied. Children (n = 246) were born of mothers enrolled in the Newborn Epigenetic Study - a prospective pre-birth cohort in the Southeastern US. We characterized seven cytokines [IL-1β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 46 publications
2
27
1
Order By: Relevance
“…The perinatal period is critical for brain development. Dysregulation of maternal cytokine levels during gestation has been associated with disturbances of motor and cognitive development, leading, for instance, to cerebral palsy, learning impairments, or autism spectrum disorders 48,49 . We previously showed using the same model that in-utero GBS-exposed rats presented sexually dichotomous impairments characterised by early autistic-like traits in males – but not in females – associated with forebrain white matter tract alterations 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The perinatal period is critical for brain development. Dysregulation of maternal cytokine levels during gestation has been associated with disturbances of motor and cognitive development, leading, for instance, to cerebral palsy, learning impairments, or autism spectrum disorders 48,49 . We previously showed using the same model that in-utero GBS-exposed rats presented sexually dichotomous impairments characterised by early autistic-like traits in males – but not in females – associated with forebrain white matter tract alterations 32 .…”
Section: Discussionmentioning
confidence: 99%
“…A more recent series of studies using this model pinpoints the role of maternal Th17 cell-derived IL-17a as critical in producing a striking cortical patching phenotype in offspring, alongside autism-like behavioral abnormalities [3436]. In contrast to these pre-clinical data, a recent study in humans links high levels of maternal IL-17a during the first trimester to better cognitive outcomes in children by 4 years of age, rather than the opposite [37]. Nonetheless, this is a promising avenue of research, as IL-17a could be an important therapeutic target to pursue.…”
Section: Environmental Factors Affecting Microglial Developmentmentioning
confidence: 99%
“…Common to these conditions are increased levels of maternal cytokines. Studies of multiple independent cohorts have identified an association between altered maternal gestational serum cytokines and adverse neurodevelopmental outcomes in the child [ 10 , 11 ]. In experimental models, MIA increases levels of inflammatory cytokines, including tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), IL-1β, IL-17A, and interferon-gamma (IFN-γ) in maternal serum, the placenta, amniotic fluid, and fetal brain after immune insult [ 8 , 12 15 ], and specific cytokines, for example IL-1 [ 16 ], IL-6 [ 17 ], and IL-17A [ 13 ], have been identified as essential in mediating the effects of MIA on offspring behavior.…”
Section: Introductionmentioning
confidence: 99%